2016
DOI: 10.18632/oncotarget.11676
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells from human glioblastoma resemble but do not mimic original tumors after in vitro passaging in serum-free media

Abstract: Human gliomas harbour cancer stem cells (CSCs) that evolve along the course of the disease, forming highly heterogeneous subpopulations within the tumour mass. These cells possess self-renewal properties and appear to contribute to tumour initiation, metastasis and resistance to therapy. CSC cultures isolated from surgical samples are considered the best preclinical in vitro model for primary human gliomas. However, it is not yet well characterized to which extent their biological and functional properties cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 28 publications
(37 reference statements)
3
34
0
Order By: Relevance
“…6L and M), which suggest that Tau represses the growth of EGFRamp/wt glioma growth by blocking the plasticity of tumor cells and the appearance of mesenchymal features. Previous results from our group and others have shown that, in comparison with PN cancer stem cells (CSCs), MES CSCs are more capable of glioma initiation, probably associated with their increased angiogenic capacity (22,23). In agreement with this observation, the overexpression of Tau in RG1 cells impaired their capacity to form subcutaneous xenografts ( fig.…”
Section: Tau Blocks the Mesenchymalization Of Egframp/wt Glioma Cellssupporting
confidence: 85%
“…6L and M), which suggest that Tau represses the growth of EGFRamp/wt glioma growth by blocking the plasticity of tumor cells and the appearance of mesenchymal features. Previous results from our group and others have shown that, in comparison with PN cancer stem cells (CSCs), MES CSCs are more capable of glioma initiation, probably associated with their increased angiogenic capacity (22,23). In agreement with this observation, the overexpression of Tau in RG1 cells impaired their capacity to form subcutaneous xenografts ( fig.…”
Section: Tau Blocks the Mesenchymalization Of Egframp/wt Glioma Cellssupporting
confidence: 85%
“…H&E staining of the nodular xenograft portion and of the original patient tumor indicated that the boundary of the xenograft was clear, whereas in the original patient tumor, the boundaries were unclear. Although there was only one case with nodular growth, it was reported that gliomas had nodular growth in mice models and had relatively clear boundaries with normal brain tissue (31)(32)(33). These results show there were notable differences in the MRI characteristics between patient-derived orthotopic xenograft models and the corresponding original tumors.…”
Section: Discussionmentioning
confidence: 70%
“…CSCs possess biological characteristics such as rapid repair of damaged DNA [ 12 , 13 ], metabolic reprogramming [ 14 ], adaption to hyperinflammatory microenvironments [ 10 ], and resistance to oxidative stress and anticancer drugs [ 10 , 15 ]. Evidence indicates that malignant glioma CSCs induce cancer and promote cancer development [ 16 , 17 ]. Moreover, glioma CSCs promote cancer resistance to treatment and recurrence, leading to high mortality [ 18 ].…”
Section: Introductionmentioning
confidence: 99%